Mental Health and Health Behaviors of the Population Under the COVID-19 Pandemic: A Case Study of Wiang Nue Community, Chiang Rai Province - Janpipatpong, Tanapat; Prasunin, Jamaree; Fongissara, Noppachai (RMUTK Journal of Liberal Arts, 2024)
Under the pressure during the COVID-19 pandemic situation, it affected to mental health of the population, particularly in semi-urban and rural areas. This correlational-comparative research aims 1) to compare and 2) to study correlation between mental health and health behaviors of Wiang Nue Community, Wiang Chai District, Chiang Rai province, categorized based in sleep hours. Data. was collected from 244 individuals using a reliable measurement instrument with a confidence interval between .686 and .909. The sample size was calculated using G*Power software, employing simple random sampling. The results showed that: 1) overall, the mental health of the Wiang Nuea community residents is better than the general population, with significantly healthier health behaviors. 2) Individuals with different hours of sleep exhibit different health behaviors. This research underscores the importance of further research and community health development in the future.